STOCK MARKET INTEGRATION BETWEEN MALAYSIA AND INDONESIA - Tongku, Christopher (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
This research is done to prove the integration market betweenIndonesian and Malaysian composite index. In this research, it used the GARCHmodel because of the classic assumption test of non heteroscedasticity model arenot fulfilled. The research is quantitative research. It used the data from yahoofinance starting on January 2008 until December 2012. The samples used in thisresearch are 1220 data from each Indonesian and Malaysian return price in dailybasis. The data was processed into several test and hypothesis. The researchresults indicates that Malaysian composite index have a significant impact onIndonesian composite index in the same day. The data will be useful for investorto predict the return of Indonesian composite index.